Asceticism, Fieldwork and Technologies of the Self in Latin American Catholic Monasticism - Ludueña, Gustavo Andrés (Fieldwork in religion, 2005)
This article analyses and proposes a methodological strategy—namely, adaptation-participation—for approaching ethnographically religious settings. This procedure is based on the adoption of native technologies of the self for reaching the numinous, which supposes a process of accommodation and re-socialization of the ethnographer to the field. By focusing on ascetic technologies carried out in Benedictine monastic communities of Latin America—i.e., silence and lectio divina-this study demonstrates how their use for social research grants ethnographic entrance into the cultural milieu of monasteries. In this sense, this investigation also reveals closeness between asceticism and fieldwork defined by the Socratic principle of care of oneself, which is constituted by technologies that subjects carry on over themselves. To summarize, this work argues that the adoption of vernacular technologies of the self through adaptation-participation bridges ontologies between fieldworker and Other's culture by producing intimacy with subjects' experience. This strategy of adaptation-participation might also be applied in non-monastic contexts or, rather, not necessarily religious contexts.